Multi Grain‐Size Total Sediment Load Model Based on the Disequilibrium Length. Issue 11 (24th November 2022) - Le Minor, Marine; Davy, Philippe; Howarth, Jamie; Lague, Dimitri
Abstract: In natural rivers, sediment heterogeneity and flow variability control the diversity of transport modes that occur. Although these different modes contribute to the total sediment transport, a law extending from bed load to suspended load that is, relevant for a wide range of sediment mixtures and flow conditions is lacking. Besides, a transport‐limited assumption is often made in modeling of fluvial morphodynamics and thus potentially misses under‐/over‐capacity regimes associated with a particular range of grain sizes and hydraulic conditions. We present a Multi Grain‐Size Total Load model based on widely accepted concepts of sediment transport and developed within the transport length framework in combination with an erosion‐deposition formulation. The new transport length model captures the diversity of transport modes as a physical continuum. Transport capacities for single or bimodal grain sizes are reasonably predicted when compared to published data and scale with the bed shear stress through a continuously varying exponent linked to the characteristic transport height. Modeled transport lengths extend over several orders of magnitude at given flow conditions. Extremely long distances suggest that suspended transport is probably never at capacity. The model can be extended to populations of various grain sizes with a threshold of motion corrected from hiding‐exposure. However, further experimental constraints are needed to better describe entrainment and saltation in strongly heterogeneous bed load transport. The new theoretical formalism we introduce paves the way for a Multi Grain‐Size Total Load Sediment Transport model that includes the variety of transport modes in both non‐stationary and stationary regimes. Plain Language Summary: In natural rivers, flow variability and sediment heterogeneity affect how sediment grains are transported. Whether grains move close to the bed or higher in the water column, they all contribute to the total sediment transport as bed load and suspended load, respectively. However, a unique law that predicts the total amount of sediment that can be transported by a river for a wide range of sediment mixtures and flow conditions is lacking. Besides, in modeling of fluvial morphodynamics, the river is often assumed at capacity, meaning that it carries the maximum sediment load it can, and thus under‐/over‐capacity regimes are potentially missed. We present a Multi Grain‐Size Total Load model, built by bringing together widely accepted concepts of sediment transport, that includes the variety of transport modes in both capacity and under‐/over‐capacity regimes. The two main components of this model are: (a) the transport length defined as the distance over which sediments are transported and (b) the erosion‐deposition formulation that explicitly describes the transfer of sediment from the sediment bed to the above water column, and conversely. While the new transport length model captures the transport from bed load to suspension continuously, the erosion‐deposition model applies to several grain sizes. Key Points: Emergence of a continuous description of sediment transport using the transport length model and the erosion‐deposition framework Unified theory of sediment transport encompassing the diversity of transport modes such as bed load and suspended load Model applicable to both non‐stationary and stationary regimes while showing that transport in suspension is likely never at capacity